Furniture Music. - Ciaramitaro, Mario; Giacconi, Riccardo; Marzin, Giulia; Zoico, Daniele ([S.l.] : [s.n.], 2008)
Bernardini, Nicola ; Bertrand, Solène ; Boeri, Stefano ; Cappelletti, Francesca ; Capellini, Giulio ; De Nardo, Massimo ; Dorfles, Gillo ; Gamper, Martino ; Herrenknecht, Joa ; Hoet, Jan et al.
The book Furniture Music, which will be presented during the show, is an instrument for research. The included essays and interviews investigate the sphere of cultural production in domestic space throughout a series of subjects: the relationship between art and domesticity, the modalities of contemporary inhabitation, the cultural and political status of furniture and design. The book features interviews with Stefano Boeri, Francesca Cappelletti, Giulio Cappellini, Gillo Dorfles, Martino Gamper, Joa Herrenknecht, Jan Hoet, Eva Marisaldi, Hans Ulrich Obrist, Raqs Media Collective, Felix Vogel and essays by Nicola Bernardini, Solène Bertrand, Massimo De Nardo, Cornelia Lauf, Sam Thorne, Daniela Zangrando. (provided by publisher)
boek
Keywords: Blauer Hase